Nationwide investigation of the pyrethroid susceptibility of mosquito larvae collected from used tires in Vietnam. - Hitoshi Kawada; Yukiko Higa; Yen T Nguyen; Son H Tran; Hoa T Nguyen; Masahiro Takagi (Public Library of Science (PLoS), 2009)
Pyrethroid resistance is envisioned to be a major problem for the vector control program since, at present, there are no suitable chemical substitutes for pyrethroids. Cross-resistance to knockdown agents, which are mainly used in mosquito coils and related products as spatial repellents, is the most serious concern. Since cross-resistance is a global phenomenon, we have started to monitor the distribution of mosquito resistance to pyrethroids. The first pilot study was carried out in Vietnam. We periodically drove along the national road from the north end to the Mekong Delta in Vietnam and collected mosquito larvae from used tires. Simplified susceptibility tests were performed using the fourth instar larvae of Aedes aegypti, Aedes albopictus, and Culex quinquefasciatus. Compared with the other species, Ae. aegypti demonstrated the most prominent reduction in susceptibility. For Ae. aegypti, significant increases in the susceptibility indices with a decrease in the latitude of collection points were observed, indicating that the susceptibility of Ae. aegypti against d-allethrin was lower in the southern part, including mountainous areas, as compared to that in the northern part of Vietnam. There was a significant correlation between the susceptibility indices in Ae. aegypti and the sum of annual pyrethroid use for malaria control (1998-2002). This might explain that the use of pyrethroids as residual treatment inside houses and pyrethroid-impregnated bed nets for malaria control is attributable to low pyrethroid susceptibility in Ae. aegypti. Such insecticide treatment appeared to have been intensively administered in the interior and along the periphery of human habitation areas where, incidentally, the breeding and resting sites of Ae. aegypti are located. This might account for the strong selection pressure toward Ae. aegypti and not Ae. albopictus.